Reflection mode imaging with nanoscale resolution using a compact extreme ultraviolet laser - Kondratenko, V. V., author; Pershyn, Y. P., author; Artioukov, I. A., author; Vinogradov, A. V., author; Attwood, D. T., author; Anderson, E. H., author; Liddle, J. A., author; Chao, W., author; Rocca, Jorge J., author; Marconi, M. C., author; Menoni, C. S., author; Grisham, M., author; et al. (Colorado State University. Libraries, 2005)
We report the demonstration of reflection mode imaging of 100 nm-scale features using 46.9 nm light from a compact capillary-discharge laser. Our imaging system employs a Sc/Si multilayer coated Schwarzschild condenser and a freestanding zone plate objective. The reported results advance the development of practical and readily available surface and nanostructure imaging tools based on the use of compact sources of extreme ultraviolet light.